Recall in Germany: explaining the use of a local democratic innovation. Issue 8 (17th November 2018) - Geissel, Brigitte; Jung, Stefan
ABSTRACT: While recall recently has gained slightly more attention from academia, the use of recall has hardly been under systematic scrutiny. Our study tackles this research gap and seeks to answer the following question: What combinations of conditions facilitate or constrain the use of local recall (in Germany)? It provides a qualitative comparative analysis of conditions of recall use in 11 German federal states. Building on theories of democratic innovations and previous studies on recall, we develop an analytic framework systematizing the conditions we include in our empirical analysis along three dimensions: institutional design, attitudinal context, and political context. While our article focuses on Germany, our analytic framework can be applied to study recall in other countries and on other levels, allowing for more systematic comparative research. Applying fuzzy-set qualitative comparative analysis, our article provides a comprehensive picture explaining the use of recall. It shows that political and attitudinal conditions serve as an equally important explanation for recall use as the institutional design of recall does. Our article gives new insights considering the conditions for the use of direct democratic instruments.